111k views
5 votes
Which expressions are equivalent to…

Which expressions are equivalent to…-example-1

2 Answers

0 votes

Answer: E.

Explanation:


\displaystyle\\(5)/(6) (18x^2-3x)-(6)/(5) (5x^3-10x-30x^2)=\\\\(5)/(6)(18)(x^ 2)-(5)/(6) (3)(x)-(6)/(5) (5)(x^3)+(6)/(5)(10)(x)+(6)/(5) (30)(x^2)=\\\\ (5*18)/(6) x^2-(5*3)/(6)x -(6*5)/(5) x^3+(6*10)/(5)x+(6*30)/(5) x^2=\\\\5*3*x^2-(5)/(2) x-6x^3+6*2*x+6*6*x^2=\\\\15x^2-(5)/(2)x-6x^3+12x+36x^2=\\ -6x^3+51x^2-(5)/(2) x+12x

User Rahul Uttarkar
by
4.9k points
3 votes

Answer: E

Explanation:


(5)/(6)(18x^(2) -3x)-(6)/(5) (5x^(3) -10x-30x^(2) )


=(5)/(6)(18x^(2)) + (5)/(6) (-3x) - (6)/(5) (5x^(3) )-(6)/(5) (-10x)-(6)/(5) (-30x^(2) )


= 15x^(2) -(5)/(2) x-6x^(3) +12x+36x^(2)


=-6x^(3) + (15x^(2) +36x^(2) )+(-(5)/(2)x+12x)


=-6x^(3) + 51x^(2) -(5)/(2)x+12x

Therefore, the answer is E.

User Crazy Cat
by
4.4k points